2007
DOI: 10.1209/0295-5075/78/56004
|View full text |Cite
|
Sign up to set email alerts
|

Planar channeling radiation from electrons in quartz

Abstract: The possibility to stimulate channeling radiation by external excitation of ultrasonic waves in a piezoelectric single crystal is predicted by theory. The experimental verification of this effect requires the knowledge of the undisturbed spectrum of channeling radiation. For the first time, planar channeling radiation from 17, 25 and 32 MeV electrons channeled in a quartz single crystal has been measured. The analysis performed bases on the application of the theory of channeling radiation. Real planar continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The initial studies have shown that the intensity of ChR can be increased if the oscillatory motion of the particles in the channel is in resonance with ultrasonic waves (US) excited in the crystal [16]. This feature has been further confirmed in references [26][27][28][29][30][31][32] within the framework of quasi-classical mechanics and electrodynamics. The consistent quantum theory for the influence of US on the ChR from electrons and positrons has been developed after 2000 and published in a series of papers, mostly by the IAPP employees [17][18][19][20][21][22][23][24][25].…”
Section: Chr In the Presence Of Acoustic Waves In Crystalsmentioning
confidence: 88%
See 1 more Smart Citation
“…The initial studies have shown that the intensity of ChR can be increased if the oscillatory motion of the particles in the channel is in resonance with ultrasonic waves (US) excited in the crystal [16]. This feature has been further confirmed in references [26][27][28][29][30][31][32] within the framework of quasi-classical mechanics and electrodynamics. The consistent quantum theory for the influence of US on the ChR from electrons and positrons has been developed after 2000 and published in a series of papers, mostly by the IAPP employees [17][18][19][20][21][22][23][24][25].…”
Section: Chr In the Presence Of Acoustic Waves In Crystalsmentioning
confidence: 88%
“…For explanations see [20]. The results obtained in [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] can be used to control the parameters of ChR and for the enhancement of its intensity.…”
Section: 2mentioning
confidence: 99%
“…This interplay is very pronounced in quartz. It, e.g., enables the observation of rather intense CR even out of planes with relatively large indices [52]. A variety of crystallographic planes in quartz are illustrated in figure 2, which shows the zone of the x-cut axis [2 1 1 0].…”
Section: Structure Of a Quartz Single Crystalmentioning
confidence: 99%
“…In this work, we present the results of a series of CR measurements on quartz performed for the first time at medium electron energies at the radiation source ELBE [50]. Planar CR has been generated at beam energies between 17 and 32 MeV in nearly all crystallographic planes which are accessible at an x-cut quartz single crystal and where CR occurs with measurable intensity [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…In such crystals, intense CR is observed from channeling along planes with small indices such as (100), (110) and (111). In our previous papers [16,17] we investigated CR generated in different planes of a quartz crystal (SiO 2 ) which has a hexagonal structure. The more complicate structure of the binary quartz crystal (compared with cubic crystals such as, e.g., diamond, Si or Ge) allows for planes with relatively large indices, which have rather deep continuum potentials favouring CR emission.…”
Section: Introductionmentioning
confidence: 99%